IMPLEMENTASI MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTUAN CANVA DALAM MENINGKATKAN MINAT BELAJAR SEJARAH KEBUDAYAAN ISLAM SISWA KELAS VIII MADRASAH TSANAWIYAH LABORATORIUM KOTA JAMBI - Winda; Kurniawan, Yudi; Ridwan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning interest in Islamic Cultural History (Sejarah Kebudayaan Islam) through the implementation of animated video learning media assisted by the Canva application. The research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects of this study were 22 eighth-grade students of MTs Laboratorium Kota Jambi in the academic year 2025/2026. Data were collected through observation sheets, questionnaires on learning interest, interviews, and documentation. The indicators of learning interest measured in this study included students’ enjoyment, attention, active participation, and motivation during the learning process. The results showed a significant improvement in students’ learning interest after the implementation of animated video media assisted by Canva. In Cycle I, students’ learning interest increased moderately, while in Cycle II it reached the expected success criteria with a percentage above 80%. These findings indicate that the use of Canva-assisted animated video learning media can create an engaging and interactive learning atmosphere, thereby effectively increasing students’ learning interest in Islamic Cultural History. Therefore, this media can be recommended as an alternative innovative learning strategy to enhance students’ engagement in the classroom.